631Benefits of not smoking during pregnancy for Aboriginal women and their babies. (2nd September 2021) - Torvaldsen, Siranda; Ibiebele, Ibinabo; Ford, Jane; Randall, Deborah; Morris, Jonathan; Meharg, David; Mitchell, Jo; Milat, Andrew; Torvaldsen, Siranda
Abstract: Background: To provide evidence for targeted smoking cessation policy, the aim of this study was to compare pregnancy outcomes of Aboriginal mothers who reported not smoking during pregnancy with those who reported smoking. Methods: This population-based retrospective cohort study used linked data from routinely collected datasets. Not smoking during pregnancy was the exposure of interest among all New South Wales Aboriginal women who became mothers of singleton babies in 2010–2014. Unadjusted and adjusted relative risks (aRR) and 95%CIs from modified Poisson regression were used to examine associations between not smoking during pregnancy and maternal and perinatal outcomes including severe morbidity, inter-hospital transfer, perinatal death, preterm birth and small-for-gestational age. Population attributable fractions (PAFs) were calculated using adjusted relative risks. Results: Compared with babies born to mothers who smoked during pregnancy, babies born to non-smoking mothers had a lower risk of all adverse perinatal outcomes including perinatal death (aRR=0.58, 95%CI 0.44–0.76), preterm birth (aRR=0.58, 95%CI 0.53–0.64) and small-for-gestational age (aRR=0.35, 95%CI 0.32–0.39). PAFs(%) were 27% for perinatal death, 26% for preterm birth and 48% for small-for-gestational-age. Compared with women who smoked during pregnancy (n = 8, 919), those who did not smoke (n = 9, 235) had a lower risk of being transferred to another hospital (aRR=0.76, 95%CI 0.66–0.89). Conclusions: Babies born to women who did not smoke had much lower risks of all adverse perinatal outcomes. Key messages: Between a quarter and a half of adverse perinatal outcomes in this population could potentially be prevented by an effective smoking cessation program.